Knowledge of the Three-Tier Pension Scheme and its Influence on Retirement Planning among Workers in Selected Organizations in Ghana - Ayi-Bonte, M. (University of Ghana, 2013)
The study investigates the relationship between knowledge of the three-tier pension scheme and retirement planning. Using the cross sectional survey method, 196 participants made up of 102 males and 94 females were sampled from six organisations. Participants were administered with the Retirement Planning Scale, Knowledge of the three-tier pension Scheme questionnaire and the Financial Literacy Questionnaire. The result using Pearson Product-Moment Correlation Coefficient indicates that knowledge of the three-tier pension scheme has a significant positive correlation with retirement planning. Also, significant age difference was found among respondents however, gender did not yield any significant difference among respondents in relation to their knowledge of pension scheme and retirement planning using the Independent t-test. Further analysis using the hierarchical multiple regression showed that variables such as age, educational level, income level and financial literacy had significant moderation effects on the relationship between knowledge of the three-tier pension scheme and retirement planning. These findings imply that for workers to better plan for retirement they must possess adequate knowledge of their pension scheme. They also need not to underplay the importance of the moderating variables (that is, financial literacy, educational level, income level and age) during the process of planning. It is therefore essential for employers to organize workshops or seminars to educate their employees on their pension schemes, identify the prospects and challenges associated with the scheme early enough to assist workers to make informed decisions about their retirement.
Thesis (MPhil) - University of Ghana, 2014